Carbon‐Based Materials as Lithium Hosts for Lithium Batteries. Issue 51 (18th July 2022) - Chen, Shang; Chen, Shuiyin; Han, Dengji; Bielawski, Christopher W.; Geng, Jianxin
Abstract: Lithium (Li) metal has attracted significant attention in areas that range from basic research to various commercial applications due to its high theoretical specific capacity (3860 mA h g −1 ) and low electrochemical potential (−3.04 vs. standard hydrogen electrode). However, dendrites often form on the surfaces of Li metal anodes during cycling and thus lead to battery failure and, in some cases, raise safety concerns. To overcome this problem, a variety of approaches that vary the electrolyte, membrane, and/or anode have been proposed. Among these efforts, the use of three‐dimensional frameworks as Li hosts, which can homogenize and minimize the current density at the anode surface, is an effective approach to suppress the formation of Li dendrites. Herein, we describe the development of using carbon‐based materials as Li hosts. While these materials can be fabricated into a variety of porous structures, they have a number of intrinsic advantages including low costs, high specific surface areas, high electrical conductivities, and wide electrochemical stabilities. After briefly summarizing the formation mechanisms of Li dendrites, various methods for controlling structural and surface chemistry will be described for different types of carbon‐based materials from the viewpoint of improving their performance as Li hosts. Finally, we provide perspective on the future development of Li host materials needed to meet the requirements for their use in flexible and wearable devices and other contemporary energy storage techniques. Abstract : Owing to their low costs, high specific surface areas, high electrical conductivities, and wide electrochemical stabilities, carbon‐based materials are prime candidates for use as Li hosts. This concept article describes a series of structurally‐unique carbon‐based materials that have been used in Li storage applications and includes an examination of the underlying mechanisms of Li dendrite growth and suppression as well as an outlook for the field.